1981
DOI: 10.1161/01.hyp.3.3_pt_2.i30
|View full text |Cite
|
Sign up to set email alerts
|

Detection and isolation of inactive, large molecular weight renin in human kidney and plasma.

Abstract: Estimation of apparent molecular weight (raw) of inactive renin by gel filtration of human plasma was found to be inaccurate when "acid activation" or "cryoactivation" was used for detection; recoveries were only 5% to 20%. Trypsln activation produced greater recoveries, but the apparent elution volume of inactive renin varied with the concentration of trypsln used; the presence of trypsln inhibitors increased trypsin requirements to 100 to 200 Mg/ml in the 60,000 dalton region, while low protein concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…These similarities have emerged despite the use of only partially purified preparations of plasma and renal inactive renin, which could contain variable quantities of enzymes and other proteins that might affect activation and characterization. These findings are consistent with the postulate that plasma inactive renin arises from the kidney and are supported (a) by the present observations demonstrating a gradient of inactive renin in IVC and renal vein blood and (b) by the report of Atlas et al (8) who found inactive renin in the perfusate of an isolated human kidney.…”
Section: Inactive Renin In Human Plasmasupporting
confidence: 93%
See 3 more Smart Citations
“…These similarities have emerged despite the use of only partially purified preparations of plasma and renal inactive renin, which could contain variable quantities of enzymes and other proteins that might affect activation and characterization. These findings are consistent with the postulate that plasma inactive renin arises from the kidney and are supported (a) by the present observations demonstrating a gradient of inactive renin in IVC and renal vein blood and (b) by the report of Atlas et al (8) who found inactive renin in the perfusate of an isolated human kidney.…”
Section: Inactive Renin In Human Plasmasupporting
confidence: 93%
“…The use of different activation techniques may have resolved some of the molecular weight discrepancies previously reported between plasma and renal inactive renin (8,9). Several methods used in this study also emphasize the heterogeneity of human inactive renin.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Inactive renin can be activated in vitro by acidification to pH 3.3 or by treatment with certain proteolytic enzymes (1)(2)(3)(4)(5)(6)(7)(8). This substance has several chromatographic properties that clearly distinguish it from the active enzyme (8)(9)(10)(11)(12)(13) and it also has a slightly greater molecular weight by gel filtration (8,(12)(13)(14).…”
mentioning
confidence: 99%